DETERMINAN PENGUNGKAPAN MODAL INTELEKTUAL DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN - N Nurabiah; Lukman Effendy; Zuhrotul Isnaini (Jurnal Riset Akuntansi, 2016)
The objective of this study is to examine the influence of firm size, leverage, firm age, independent commissioners, and type of industry toward influence of intellectual capital disclosure. The study also aimed to examine the intellectual capital disclosure toward the firm’s value. The sample of this study is consisted of companies listed in the Kompas 100 index during the period of 2013- 2015, so that this study obtained a total observation of 156 units. This research was conducted based on documentation, while data is acquired through the Indonesian Capital Market Directory (ICMD) and Indonesia Stock Exchange (IDX) Fact. Data were analyzed based on multiple linear regression, t-test and F-test. The results of the analysis in this study indicate that the leverage, independent commissioners, and type of industry have significant influence on the intellectual capital disclosure while firm size and firm age does not have significant influence on the intellectual capital disclosure. The results also showed that the intellectual capital disclosure has no significant influence on the firm’s value. Keywords: firm size, leverage, firm age, independent commissioners, type of industry, intellectual capital disclosure, firms value